Structured clinical reasoning for exercise prescription in patients with comorbidity. Issue 10 (7th May 2020) - van der Leeden, Marike; Stuiver, Martijn M.; Huijsmans, Rosalie; Geleijn, Edwin; de Rooij, Mariëtte; Dekker, Joost
Abstract: Purpose: Exercise therapy is an effective intervention in a variety of chronic diseases. The prescription of exercise therapy is usually directed toward an index disease. The presence of comorbidity may require adaptations to the exercise program as intended for the index disease. This paper aims to structure the clinical reasoning process of health professionals when prescribing exercise therapy for the individual patient with an index disease and comorbidity. Methods: We adapted the previously published strategy for developing guidelines and protocols on comorbidity-adapted exercise to a version that can be used for individual exercise prescription. Results: Essential steps and considerations involved in prescribing an exercise program to an individual patient with comorbidity are described. A case description is used as an example of how the proposed strategy leads to clinical decisions. Conclusions: The proposed strategy may have a role in educational and professional development. The advanced clinical expertise needed for safe and effective exercise therapy in patients with a complex health status is emphasized. Implications for Rehabilitation: The presence of comorbidity may require adaptations to exercise therapy. We describe the essential steps and considerations involved in prescribing an exercise program to an individual patient with an index disease and comorbidity. The proposed strategy can be used to structure the clinical reasoning process of health professionals.